Effects of frequently prescribed antiseizure medications on motor vehicle driving performance: Narrative review based on a tiered approach for the assessment of clinically meaningful driving impairment in the Ministry of Health, Labour, and Welfare guideline - Kunihiro Iwamoto; Tetsuo Nakabayashi; Akiko Yamaguchi; Yuki Konishi; Momoe Saji; Reiji Yoshimura; Kousuke Kanemoto; Hirofumi Aoki; Masahiko Ando; Norio Ozaki (Neuropsychopharmacology Reports)
Abstract Patients with epilepsy often require long‐term treatment with antiseizure medications, and their impact on daily activities, particularly driving, is of significant concern. The recently published “Guideline for Evaluating Effects of Psychotropic Drugs on the Performance to Drive a Motor Vehicle” in Japan provides a framework that can be referred to for not only the evaluation of new drugs but also the reevaluation of approved drugs. This study conducted a literature review regarding the effects of carbamazepine, valproate, lamotrigine, lacosamide, and levetiracetam, which are frequently prescribed for epilepsy, on driving performance following the guideline's tiered evaluation approach. Analyses of pharmacological, pharmacodynamic, and adverse events suggested that these drugs primarily affect arousal function. Driving studies showed that acute administration of carbamazepine, but not chronic monotherapy with carbamazepine, valproate, lamotrigine, and levetiracetam, significantly impairs driving performance. Epidemiological studies have not identified a definitive association between these drugs and traffic accidents. Initial administration of these five antiseizure medications may affect driving performance, warranting special attention, but the influence appears to diminish with continued use. Nevertheless, while long‐term administration of these five drugs may not have a clinically meaningful effect on driving performance, safe driving is not guaranteed for each individual patient, and appropriate individualized guidance is important in clinical practice.